PENGARUH LIKUIDITAS, LEVERAGE DAN CASH FLOW RETURN ON ASSETS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - B31111007, MEGA YULIANA (Jurnal Manajemen Update, 2016)
Dividend policy determines profit-placement, whether paid it to shareholders or making it as investment for company. Retained earnings is one of most important funding for company, but dividend is a cash flow should be set asside for shareholders. This research aimed to analyze liquidity, leverage, and cash flow return on assets that affect dividend policy on manufacturing companies listed on Indonesia Stock Exchange (IDX) in 2009-2013. Population in this research were 141 manufacturing companies listed on Indonesia Stock Exchange (IDX) in 2009-2013. Samples collected as many as 34 companies selected by porposive sampling. Independent variables in this research is Liquidity (Current Ratio), Leverage (Debt to Equity Ratio), and Cash Flow Return On Assets (ROA), while the dependent variable is Dividend Policy (Dividend Payout Ratio). The method used for analysis in this research is multiple linear regression. The results showed that both Liquidity and Leverage has insignificant effect on Dividend Policy, meanwhile Cash Flow Return On Assets has significant effect on this dependent variable. Coefficient of determination is 4.3%. That result indicates the magnitude of the ability of independent variables explain dependent variable, while the 95.7% explained by other variables. Key Word : Liquidity, Leverage, Cash Flow Return on Assets, and Dividend           Policy.